Interdisciplinarity as cognitive integration: auditory verbal hallucinations as a case study. Issue 5 (31st July 2014) - Bernini, Marco; Woods, Angela
Abstract : In this article, we advocate a bottom‐up direction for the methodological modeling of interdisciplinary research based on concrete interactions among individuals within interdisciplinary projects. Drawing on our experience in Hearing the Voice (a cross‐disciplinary project on auditory verbal hallucinations running at Durham University), we focus on the dynamic if also problematic integration of cognitive science (neuroscience, cognitive psychology, and of mind), phenomenology, and humanistic disciplines (literature, narratology, history, and theology). We propose a new model for disciplinary integration which brings to the fore an under‐investigated dynamic of interdisciplinary projects, namely their being processes of distributed cognition and cognitive integration. WIREs Cogn Sci 2014, 5:603–612. doi: 10.1002/wcs.1305 This article is categorized under: Philosophy > Knowledge and Belief